Deciphering Seed Deterioration: Molecular Insights and Priming Strategies for Revitalizing Aged Seeds - Weigeng Xing; Yi Li; Linyan Zhou; Hao Hong; Yuan Liu; Shuailong Luo; Jialong Zou; Yan Zhao; Yanfei Yang; Zhenjiang Xu; Bin Tan (Plants)
Seed deterioration is an inevitable process during storage, characterized by a gradual loss of germination capacity and eventual seed death, which poses challenges to seed longevity and the preservation of genetic resources. Understanding the molecular mechanisms driving seed aging and inherent resistance pathways, alongside developing innovative rejuvenation strategies for deteriorated seeds, is crucial for agricultural sustainability and germplasm banking. This review systematically examines (1) redox-regulated deterioration pathways involving reactive oxygen species (ROS) and macromolecular damage cascades, (2) anti-deterioration mechanisms mediated by the antioxidant system and macromolecular repair mechanisms, (3) genetic–epigenetic networks governing seed aging resistance, particularly ABA- and IAA-mediated signaling through ABI3/ABI5/LEC1 regulons, and (4) technological advances in seed priming that restore aged seeds via metabolic resetting and repair potentiation. By integrating multi-omics insights with physiological evidence, we propose a hierarchical model of seed deterioration and establish mechanistic links between priming interventions and longevity enhancement. These insights offer a theoretical framework for cultivating anti-deterioration crop varieties and developing seed longevity-enhancement technologies.